Adolescent Self Disclosure in Non-Functional Family Situations due to Infidelity Case Study in Lamongan Regency - Ririn Puspita Tutiasri; Nadhifah Bernice Tsaniyah (Lavish Opulent Education, 2025)
This study explores self-disclosure among adolescents who experience dysfunctional family dynamics due to parental infidelity, specifically in the cultural context of Lamongan, Indonesia. The research highlights how adolescents negotiate personal boundaries in sharing their emotional experiences within interpersonal relationships. Using a qualitative descriptive approach, the study involved in-depth interviews with seven adolescents aged 17–22 who have experienced direct or indirect consequences of parental infidelity. Findings reveal that adolescents tend to be selective in their self-disclosure, particularly when interacting with new acquaintances. In early interactions, they only share surface-level information such as the number of family members or parents' occupations, avoiding emotionally sensitive topics. The study shows that emotional closeness significantly influences the depth of information shared adolescents disclose more when trust and empathy are present in a relationship. Furthermore, digital media has emerged as an alternative space for self-disclosure. Some informants report greater comfort in sharing personal stories with strangers online than with close friends in real life, due to perceived anonymity and lower emotional risk. However, this behavior also poses risks related to privacy and misuse of information. The research emphasizes that self-disclosure is a gradual and context-dependent process shaped by interpersonal trust, emotional safety, and the communicative medium used. This study contributes to the understanding of adolescent psychological resilience and the role of communication in emotional recovery from family crises, highlighting the importance of creating supportive environments both offline and online.